Omalizumab-associated eosinophilic granulomatosis with polyangiitis: cause or coincidence?. Issue 7 (29th July 2021) - Carson, Luke Nessan; Pradhan, Ashish; Subramanian, Deepak
Abstract : Omalizumab is an anti-IgE monoclonal antibody used in severe allergic asthma. Herein, we describe a case of eosinophilic granulomatosis with polyangiitis, which manifested 3 months after initiation of omalizumab therapy, while maintenance corticosteroid therapy dose was unchanged.